Family farming in Western Newfoundland production and exchange strategies in a remote agricultural region - Flint, John David (Rural Research Centre, Nova Scotia Agricultural College, 1996)
This study focuses on what was once central to the development of agriculture in Newfoundland, the "family farm". The family farm is an unusual formation in a mature capitalist economy because it is both a production unit and a domestic unit. It is work site and a home site and it is often difficult to separate economic activities and relationships from domestic ones. It is a "household commodity production unit " and as such it is tempting to regard it as transitional form, a hangover from pre-capitalist times which is on the way out, a hosuehold which happens to farm. This study examines an alternative possibility, that these formations are "farms of the household type" , a form well suited to the mature capitalist economy and not a residual. Therefore this study will seek to explain variation in family farm types as successful exploitations of conditions occuring in that economy rather than as stages of decay in a transitional form. Since these farms are taken seriously, variation will be described in farming terms. A farming enterprise is organized for the production and exchange of farm products. Diversity of family farm types may be explained in terms of decision taken, for whatever reason, to pursue certain strategies of prodcution and exchange.